2023
DOI: 10.1177/20563051231179694
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Downstream Effects of Fact-Checking on Social Media: Experiments on Correction Formats, Belief Accuracy, and Media Trust

Abstract: Repeated exposure to misinformation not only reduces the accuracy of people’s beliefs, but it also decreases confidence in institutions such as the news media. Can fact-checking—journalism’s main weapon against misinformation—worsen or ameliorate distrust in journalists and the media? To answer this question, we conducted two pre-registered experiments in Chile (total N = 1,472) manipulating message and receiver factors known to regulate the persuasiveness of fact-checks: transparency elements, arousing images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 76 publications
0
1
0
3
Order By: Relevance
“…This increase in fact-checking efforts can be credited, at least in part, to their effectiveness in combating misinformation (Graves, 2018). For example, Bachmann and Valenzuela (2023) demonstrated the consistent effectiveness of fact-checking in dispelling misconceptions across various message formats, impacting trust in journalists and the media. Similarly, Zhang et al (2021) observed a positive shift in vaccine attitudes when fact-checking labels were incorporated into misinformation posts, compared to a control condition.…”
Section: Efficacy and Engagement With Fact-checked Informationmentioning
confidence: 99%
“…This increase in fact-checking efforts can be credited, at least in part, to their effectiveness in combating misinformation (Graves, 2018). For example, Bachmann and Valenzuela (2023) demonstrated the consistent effectiveness of fact-checking in dispelling misconceptions across various message formats, impacting trust in journalists and the media. Similarly, Zhang et al (2021) observed a positive shift in vaccine attitudes when fact-checking labels were incorporated into misinformation posts, compared to a control condition.…”
Section: Efficacy and Engagement With Fact-checked Informationmentioning
confidence: 99%
“…Por su parte, De keersmaecker y Roets (2017) identificaron que las correcciones son más efectivas en consumidores de información con mayores habilidades cognitivas. También se ha estudiado cómo la efectividad del fact-checking depende de las preferencias políticas de los individuos (Aruguete y Calvo, 2022;Bachmann y Valenzuela, 2023;Hameleers y van de Meer, 2020;Li et al, 2022;Shin y Thorson, 2017). Otros trabajos, como el de Chan et al (2017), han subrayado que los efectos de los desmentidos son menores cuando las audiencias han generado argumentos que apoyan la desinformación original, algo que refuerza el poder del sesgo de confirmación.…”
Section: La Lucha Contra La Desinformaciónunclassified
“…A pesar de las limitaciones que se han mencionado, la investigación está generalmente convencida de la efectividad de la verificación y los desmentidos (Bachmann y Valenzuela, 2023;Ecker et al, 2019;Li et al, 2022;Porter y Wood, 2021;Walter et al, 2021). Walter et al (2020), en uno de los metaanálisis más completos hasta la fecha, coinciden en afirmar que los efectos del fact-checking son positivos, a pesar de tener una efectividad limitada en función de las características de los consumidores.…”
Section: La Lucha Contra La Desinformaciónunclassified
See 1 more Smart Citation